Employee psychological empowerment: Psychometric properties of the Lithuanian questionnaire - Tvarijonavičius, M.; Bagdžiūnienė, D. (Psichologija, 2013)
Employee psychological empowerment is treated as a multidimensional construct manifesting in several dimensions. It has been researched for several decades using various scales depending on the definition of psychological empowerment chosen by a reasercher. However, there is a lack of widely applicable, compact instruments for a reliable and valid assessment of psychological empowerment. Furthermore, there has been a lack of empowerment research in Lithuania. Therefore, the purpose of this study is to construct a Lithuanian psychological empowerment questionnaire and to evaluate its psychometric properties (reliability and validity). The strategy of the empirical construction of a questionnaire was used. At first, statements to describe the concept of psychological empowerment were generated, using group interviews and expert evaluation. Fifteen final items were included into the Lithuanian Psychological Empowerment Questionnaire (LPEQ). Then, an empirical research was performed: 189 respondents from 8 organizations filled up the LPEQ, G.M. Spreizer (1995) Psychological Empowerment Questionnaire (PEQ), B. E. Ashforth (1990) Helplessness Scale, Intrinsic Motivation Scale (Warr et al., 1979), and socio-demografic questions. The results of the study have revealed that the LPEQ has a high internal reliability (Cronbach α = 0.909). Five factors were extracted using the exploratory factor analysis, three items each. Psychological empowerment was defined based on five dimensions: meaning, enthusiasm, decision making, authonomy, and trust in competence. The Cronbach α was between 0.755 and 0.880 for the dimension level. These five dimensions show support for the existing models of psychological empowerment (Spreitzer, 1995; Menon, 2001), but also they supplement these models with for instance, the dimension of enthusiasm. The convergent validity of the LPEQ was confirmed by strong correlations (p < 0.01) between the LPEQ and the PEQ subscales, and the Intrinsic Motivation Scale. It was supported by a negative correlation between the LPEQ subscales and the Helplessness Scale. Based on the analysis of correlations, the discriminant validity of the LPEQ dimensions’ levels was confirmed. In conclusion, the Lithuanian Psychological Empowerment Questionnaire (LPEQ) can be characterized as an instrument with appropriate psychometric properties for the use in research and practice. Directions for the future research in the field have been offered.